Exports, imports and firm survival: First evidence for manufacturing enterprises in Germany - Joachim Wagner (Institute for the Study of Labor (IZA), 2011)
This paper documents the relationship between firm survival and three types of international trade activities - exports, imports and two-way trade. It uses unique new representative data for manufacturing enterprises from Germany, one of the leading actors on the world market for goods, that merge information from surveys performed by the Statistical Offices and administrative data collected by the Tax Authorities. It contributes to the literature by providing the first evidence on the role of imports and two-way trading for firm survival in a highly developed country. Descriptive statistics and regression analysis (with and without explicitly taking the rare events nature of firm exit into account) point to a strong positive link between firm survival on the one hand and imports and two-way trading on the other hand, while exporting alone does not play a role for exiting the market or not.
urn:nbn:de:101:1-20110927527
Keywords: F14; 330; exports; imports; firm survival; Unternehmensentwicklung; Industriegüteraußenhandel; Import; Außenhandelswirtschaft; Schätzung; Deutschland